2010
DOI: 10.1158/1078-0432.ccr-10-1490
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Targeting of the Phosphatidylinositol-3 Kinase Pathway as a Strategy for Treating Melanoma

Abstract: Purpose: Melanoma is relatively resistant to chemotherapy; improved targeting of molecules critical for cell proliferation and survival are needed. Phosphatidylinositol-3 kinase (PI3K) is an important target in melanoma; however, activity of PI3K inhibitors (PI3KI) is limited. Our purpose was to assess mTOR as a cotarget for PI3K.Methods: Using a method of quantitative immunofluorescence to measure mTOR expression in a large melanoma cohort, we studied associations with PI3K subunits, p85 and p110a. We assesse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 51 publications
5
59
0
Order By: Relevance
“…Aziz et al (24) has shown dual inhibitor of PI3K/mTOR has beneficial property for treating melanoma. In addition, they have found a synergism at a concentration of 5 µmol/L LY294002 with 1, 100 and 1000 nmol/L of rapamycin in patient-derived melanoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Aziz et al (24) has shown dual inhibitor of PI3K/mTOR has beneficial property for treating melanoma. In addition, they have found a synergism at a concentration of 5 µmol/L LY294002 with 1, 100 and 1000 nmol/L of rapamycin in patient-derived melanoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Activation of PI3K is a key event for the initiation of Akt signaling in melanomas. 16,44 PI3K is activated by liganddependent activation of tyrosine kinase receptors, G-proteincoupled receptors, or integrins (Fig. 1).…”
Section: Do Not Distributementioning
confidence: 99%
“…[47][48][49] Therefore, targeting activated PI3K inhibits melanoma development. 44,50 For example, overexpression of a deleted subunit of PI3K (Deltap85) reduced PI3K signaling in the melanoma cell line G361. 51 Similarly, targeting PI3 kinase using siRNAs or pharmacological agent ZSTK474 inhibited melanoma tumor development.…”
Section: Do Not Distributementioning
confidence: 99%
See 2 more Smart Citations